Comparison of masticatory efficiency, patient satisfaction for single, two, and three implants supported overdenture in the same patient: A pilot study - Srinidhi Bhat; Ramesh Chowdhary; Sudhindra Mahoorkar (Wolters Kluwer Medknow Publications, 2016)
Statement of Problem: Over 30% of the world population suffers from edentulism. Implant supported overdenture have been a relatively successful treatment option for edentulism and have shown to slowed the rate of residual resorption and maintain the vertical height of the residual. Purpose: The purpose of this study was to measure patient masticatary efficiency and satisfaction with the mandibular one-, two-, and three-implant-retained overdenture therapy when compared with conventional denture in a the same patients. Materials and Methods: Ten complete edentulous patients, who were wearing conventional complete dentures, were involved in this study. Three single piece endosseous implant of 3.0 mm in diameter and 13 mm in length were surgically placed in the mandible in the region of B, C, and D. Mandibular denture was connected for single, two, and three implant supported overdenture periodically and checked for masticatory efficiency using a bite gauge and patient satisfaction using a questionnaire. Results: Statistical analysis was done using Wilcoxon signed rank test. Four groups of bite forces when compared to each other. Group 1 was compared with Group 2, with the statistical value showing significance. Signed rank test showed no significance (0.268) when Group 2 was compared with Group 3. When Group 3 was compared with Group 4, and Group 1 compared with Group 4, rank test showed significant values. Four groups were compared with each other for patient satisfaction, Group 1 was compared with Group 2, with the statistical value showing no significance. Conclusions: A single midline implant supported overdenture can be considered as a suitable and cost-effective treatment option over conventional denture. The study concludes that masticatory efficiency of this single midline implant supported overdenture is better than the conventional complete denture.